2019
DOI: 10.1177/0022034519858282
|View full text |Cite
|
Sign up to set email alerts
|

Third Dentition Is the Main Cause of Premolar Supernumerary Tooth Formation

Abstract: While the prevalence of supernumerary teeth (ST) is high in permanent dentition, the etiology of ST in humans remains unclear. However, multiple murine models of ST have elaborated on dated mechanisms traditionally ascribed to ST etiology: one involves the rescue of rudimental teeth, and the second considers the contribution of odontogenic epithelial stem cells. It remains unclear whether these mechanisms of ST formation in mice are applicable to humans. The third dentition is usually regressed apoptotic—that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…In recent years, there have been many studies of stem cells in relation to the development of regenerative therapies for various organs such as nephrons (the functional units of the kidney) or the pituitary gland [73,74]. We also demonstrated that OESCs may contribute to supernumerary teeth formation in cases not caused by third dentitions [55]. Multiple supernumerary teeth derived from odontogenic epithelial stem cells have the potential to erupt following the eruption of permanent teeth without dental caries and periodontal disease (Fig.…”
Section: Contribution Of Oescsmentioning
confidence: 64%
See 3 more Smart Citations
“…In recent years, there have been many studies of stem cells in relation to the development of regenerative therapies for various organs such as nephrons (the functional units of the kidney) or the pituitary gland [73,74]. We also demonstrated that OESCs may contribute to supernumerary teeth formation in cases not caused by third dentitions [55]. Multiple supernumerary teeth derived from odontogenic epithelial stem cells have the potential to erupt following the eruption of permanent teeth without dental caries and periodontal disease (Fig.…”
Section: Contribution Of Oescsmentioning
confidence: 64%
“…We have previously reported that this clinical definition would apply to at least one-third of non-syndromic multiple supernumerary teeth [54]. Recently, our investigation evaluated the proportion of collected general supernumerary teeth cases that evinced a third dentition based on the clinical definition of supernumerary teeth derived from the third dentition [55]. The frequency of supernumerary teeth considered to have been derived from the third dentition was 26 out of 78 cases [55].…”
Section: Rescue Of Rudimental Tooth Germsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the term "third dentition" has been proposed to describe supernumerary teeth that develop and appear after the completion of the usual configuration of 32 permanent teeth, representing a dental anomaly of number in the human species (1)(2)(3). Although this clinical phenomenon is relatively frequent in the global population (with an estimated prevalence between 1.5 and 3.8% in permanent dentition), the exact etiology of this anomaly remains unknown (2,4,5).…”
Section: Introductionmentioning
confidence: 99%